2000
DOI: 10.1148/radiology.215.2.r00ma24337
|View full text |Cite
|
Sign up to set email alerts
|

Appendicitis at the Millennium

Abstract: Acute appendicitis is a common clinical problem. Accurate and prompt diagnosis is essential to minimize morbidity. While the clinical diagnosis may be straightforward in patients who present with classic signs and symptoms, atypical presentations may result in diagnostic confusion and delay in treatment. Helical computed tomography (CT) and graded compression color Doppler ultrasonography (US) are highly accurate means of establishing the diagnosis. These imaging modalities have now assumed critical roles in t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

18
450
1
35

Year Published

2001
2001
2021
2021

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 537 publications
(504 citation statements)
references
References 83 publications
18
450
1
35
Order By: Relevance
“…Graded compression sonography as popularized by Puylaert [1] superadded with self localization [2] is a readily available, noninvasive, highly accurate means of diagnosing appendicitis and a variety of relevant diaseases [8]. Prospective studies have shown that the overall accuracy of US in diagnosing acute appendicitis ranges between 87-96% (sensitivity 75-90%, specificity 86-100%) with positive and negative predictive values of 91-94% and 89-97% respectively [3,4,5,12]. In experienced hands US significantly improves diagnostic accuracy in suspected appendicitis while reducing the negative laparotomy rate to 8-15% [13].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Graded compression sonography as popularized by Puylaert [1] superadded with self localization [2] is a readily available, noninvasive, highly accurate means of diagnosing appendicitis and a variety of relevant diaseases [8]. Prospective studies have shown that the overall accuracy of US in diagnosing acute appendicitis ranges between 87-96% (sensitivity 75-90%, specificity 86-100%) with positive and negative predictive values of 91-94% and 89-97% respectively [3,4,5,12]. In experienced hands US significantly improves diagnostic accuracy in suspected appendicitis while reducing the negative laparotomy rate to 8-15% [13].…”
Section: Discussionmentioning
confidence: 99%
“…The preoperative clinical diagnosis is straightforward in 70-80% cases with an overall negative appendectomy rate of 20-25% [1][2][3][4]. Accurate and prompt diagnosis followed by early surgery are essential to minimize morbidity.…”
Section: Introductionmentioning
confidence: 99%
“…The transverse outer diameter of a normal appendix was 6 mm or less. 6,8 Acute appendicitis was diagnosed when there was an incompressible appendix with a transverse outer diameter of 6 mm or greater and secondary signs, 12 which included a mural thickness of greater than 2 mm and inflamed periappendiceal hyperechoic fat. 6,8 The radiologists who performed sonography subjectively defined equivocal appendicitis when the transverse outer diameter of the appendix measured greater than 6 mm without secondary signs or when they could not identify the connection between tubular structures suggesting the presence of a distended appendix and cecum due to an unusual location of the appendix or a poor sonic window.…”
Section: Sonography and Ctmentioning
confidence: 99%
“…Para ello se utiliza la maniobra de Yódice Sammartino (palpación anoparietoabdominal). En los apéndices pelvianos, Handley ha descripto un cuadro que denominó íleo doble, que es la obstrucción del intestino delgado y el colon sigmoides al mismo tiempo [6][7][8][9][10][11][12][13][14][15] .…”
unclassified
“…Si está ubicado en la fosa ilíaca derecha, por detrás de las asas intestinales, las manifestaciones locales (defensa y contractura) son pobres y el compromiso del tránsito intestinal hará que la afectación apendicular se exprese por un síndrome oclusivo del intestino delgado [6][7][8][9][10] .…”
unclassified